2010
DOI: 10.1177/0095244310385435
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lubrication on Two-body Abrasive Wear of Sealing Elastomers Under Reciprocating Sliding Conditions

Abstract: Elastomeric seals are prone to failure caused by abrasion during sliding against rough surfaces. In this research, the two-body abrasive wear of some selected sealing elastomers (nitrile rubber, hydrogenated nitrile rubber, acrylic rubber, and fluoro rubber) in dry and lubricated conditions has been studied. The influence of three different oils (synthetic ester, polyalphaolefin, and mineral oil) on the abrasive wear of the elastomers, at varying normal load and abrasive particle size, has been studied. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Although no work has been published that has studied how friction and wear varies specifically with soot on elastomers, some work has been done using small particles [54][55][56][57][58].…”
Section: Soot Effects On Wear and Friction Of Non-metallic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no work has been published that has studied how friction and wear varies specifically with soot on elastomers, some work has been done using small particles [54][55][56][57][58].…”
Section: Soot Effects On Wear and Friction Of Non-metallic Materialsmentioning
confidence: 99%
“…Most of the work in this area suggests that the cause of abrasive wear of seal lips is mainly abrasive particles being deposited as contaminants in the lubricant [54][55][56]. Mofidi et al [57] discovered that the abrasive wear of elastomers in lubricated conditions is higher than in dry due to the weakening of the elastomer by the lubricant. The presence of lubricant in the contact prevents the particles from agglomerating, and therefore more single particles can come into the contact with the surface of the elastomer and contribute to the abrasive wear as third bodies.…”
Section: Soot Effects On Wear and Friction Of Non-metallic Materialsmentioning
confidence: 99%
“…Combing the experiment with the numerical model, the influence of the wear of the seal lip on the performance of the shaft lip seal was studied [ 18 ]. The wear properties of the seal materials were investigated by experiments, including accelerated wear [ 20 ], and two-body abrasive wear [ 21 ], and so on [ 22 , 23 ]. However, since there are many parameters to be considered and controlled in the experiments, the experimental studies are normally time consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the role of swelling should also be taken into account when evaluating rubber properties. Mofidi et al [12,13] found that, after aging in various solutions, the wear resistance of NBR would reduce. According to the investigation of Lv [14], the wear volume of the NBR swelled in cyclohexane was more serious than that of an original one.…”
Section: Introduction mentioning
confidence: 99%